THE PROBLEM OF MALARIA AND ITS ERADICATION IN THE EXTREME SALIENT OF JAVA DURING THE DUTCH COLONIAL ERA (History Department, Semarang State University and Historian Society of Indonesia, 2018)
The extreme salient of Java has often been described as ‘malarious land’ and ‘unheathy region’. Although it had a great consequences on the people’s conditions of health and socio-economy, the problem of malaria has rarely been well-understood and fairly-treated in the existing historical studies. This paper is expected to fill in the existing gap in our knowledge on the issues. By using the available historical sources, the paper seeks to elaborate the problem of malaria and its eradication efforts in the extreme salient of Java during the Dutch colonial era. The major objectives of the paper are to examine the seriousness of malaria problem existing in the region and its causes, and to elaborate the ways in which the problem of malaria was contained by the colonial authorities. It is argued that there was a significant progress in the fight against malaria and the understanding of the malaria causes and the chosen methods of eradication reflected both scientific advances and economic considerations. Kawasan ujung timur Jawa sering digambarkan sebagai 'tanah malaria' dan 'wilayah yang tidak sehat'. Meskipun mempunyai konsekuensi besar pada kondisi kesehatan dan sosial ekonomi masyarakat, masalah ini jarang dipahami dengan baik dan dibahas secara memadai dalam studi sejarah yang ada. Tulisan ini diharapkan dapat mengisi kesenjangan yang ada dalam pengetahuan kita tentang isu-isu tersebut. Dengan menggunakan sumber-sumber sejarah yang tersedia, tulisan ini berusaha menguraikan problem malaria dan upaya-upaya pemberantasannya di ujung timur Jawa pada masa penjajahan Belanda. Tujuan utama tulisan ini adalah untuk mengkaji keseriusan masalah malaria dan sebab-sebabnya di wilayah tersebut dan menguraikan cara-cara di mana masalah ini diupayakan pemecahannya oleh otoritas kolonial. Diargumentasikan bahwa ada kemajuan yang signifikan dalam perang melawan malaria dan pemahaman tentang penyebab malaria dan metode yang dipilih untuk pemberantasan mencerminkan baik kemajuan ilmiah maupun pertimbangan ekonomi.